Pengamanan Data Tekstual dengan Kombinasi Vigenere Cipher dan Caesar Cipher - Luh Arimas Pertiwi; Ngurah Agus Sanjaya ER (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Problems in data security is an important aspect in maintaining data storage, especially data stored in digital form. This is due to very rapid progress in the field of computer science with the open-system concept that has been widely used, so that this can make it easier for someone to destroy data, especially data stored in digital form without having to be known by the data custodian. In this case the researcher found a problem in using one algorithm, namely the Caesar cipher in data security, where there is a Brute force attack that tries all possible key combinations to crack a password. In the context of the Caesar Cipher, brute force can be used to try all possible shifts of letters and find a key that produces a plausible decrypted text. This study aims to maximize the security of textual data by combining two algorithms in it, in which the algorithm used is the Vigenere Cipher and the Caesar Cipher. The result of this research is that textual data that is secured becomes more difficult to understand for third parties who may want to manipulate data.